Supervisory Power Coordination Scheme to Mitigate Power Curtailment in the Application of a Microgrid - Heesang Ko (MDPI AG, 2021)
There are cases where the output of renewable eappennergy (RE) is curtailed due to an increase in the share of RE. Typically, wind power (WP) is curtailed due to oversupply and low loads at midnight. However, there are cases where the output of WP is limited during the daytime due to the increase in the share of photovoltaics (PV). In the current electricity market, as the share of PV is increased, the curtailments of WP will be increased further, which will add to the difficulties experienced by wind farm operators. This paper proposes a supervisory power coordination scheme. The main purposes are to prevent the penetration of extra power from REs into the grid; thus, the curtailments can be prevented. In order to make it feasible, the proposed scheme is to design a grid-connected microgrid system to be operated only in response to loads and virtual power plant (VPP) requests. The effectiveness of the proposed scheme was verified by simulation studies conducted in the MATLAB/Simulink environment. The verification was conducted based on the voltage criteria, such as the AC voltage regulation between ±6% of the rated AC voltage, the DC voltage regulation between ±10% of the rated DC voltage, the power balance according to variations in the loads, and VPP requests for power. The simulation showed that the proposed scheme is feasible and justifiable, not only to mitigate the power curtailment problem but also to apply different system configurations.